Oxyresveratrol-Loaded PLGA Nanoparticles Inhibit Oxygen Free Radical Production by Human Monocytes: Role in Nanoparticle Biocompatibility - Marta Donini; Salvatore Calogero Gaglio; Carlo Laudanna; Massimiliano Perduca; Stefano Dusi (Molecules, 2021)
Oxyresveratrol, a polyphenol extracted from the plant Artocarpus lakoocha Roxb, has been reported to be an antioxidant and an oxygen-free radical scavenger. We investigated whether oxyresveratrol affects the generation of superoxide anion (O2−) by human monocytes, which are powerful reactive oxygen species (ROS) producers. We found that oxyresveratrol inhibited the O2− production induced upon stimulation of monocytes with β-glucan, a well known fungal immune cell activator. We then investigated whether the inclusion of oxyresveratrol into nanoparticles could modulate its effects on O2− release. We synthesized poly(lactic-co-glycolic acid) (PLGA) nanoparticles, and we assessed their effects on monocytes. We found that empty PLGA nanoparticles induced O2− production by resting monocytes and enhanced the formation of this radical in β-glucan-stimulated monocytes. Interestingly, the insertion of oxyresveratrol into PLGA nanoparticles significantly inhibited the O2− production elicited by unloaded nanoparticles in resting monocytes as well as the synergistic effect of nanoparticles and β-glucan. Our results indicate that oxyresveratrol is able to inhibit ROS production by activated monocytes, and its inclusion into PLGA nanoparticles mitigates the oxidative effects due to the interaction between these nanoparticles and resting monocytes. Moreover, oxyresveratrol can contrast the synergistic effects of nanoparticles with fungal agents that could be present in the patient tissues. Therefore, oxyresveratrol is a natural compound able to make PLGA nanoparticles more biocompatible.